Measurement of retinal nerve fiber layer thickness in eyes with optic disc swelling by using scanning laser polarimetry and optical coherence tomography - Hata M (Dove Medical Press, 2013)
Masayuki Hata, Kazuaki Miyamoto, Akio Oishi, Yugo Kimura, Satoko Nakagawa, Takahiro Horii, Nagahisa Yoshimura Department of Ophthalmology and Visual Sciences, Kyoto University Graduate School of Medicine, Kyoto, Japan Background: The retinal nerve fiber layer thickness (RNFLT) in patients with optic disc swelling of different etiologies was compared using scanning laser polarimetry (SLP) and spectral-domain optical coherence tomography (OCT). Methods: Forty-seven patients with optic disc swelling participated in the cross-sectional study. Both GDx SLP (enhanced corneal compensation) and Spectralis spectral-domain OCT measurements of RNFLT were made in 19 eyes with papilledema (PE), ten eyes with optic neuritis (ON), and 18 eyes with nonarteritic anterior ischemic optic neuropathy (NAION) at the neuro-ophthalmology clinic at Kyoto University Hospital. Differences in SLP (SLP-RNFLT) and OCT (OCT-RNFLT) measurements among different etiologies were investigated. Results: No statistical differences in average OCT-RNFLT among PE, ON, and NAION patients were noted. Average SLP-RNFLT in NAION patients was smaller than in PE (P<0.01) or ON (P=0.02) patients. When RNFLT in each retinal quadrant was compared, no difference among etiologies was noted on OCT, but on SLP, the superior quadrant was thinner in NAION than in PE (P<0.001) or ON (P=0.001) patients. Compared with age-adjusted normative data of SLP-RNFLT, average SLP-RNFLT in PE (P<0.01) and ON (P<0.01) patients was greater. Superior SLP-RNFLT in NAION patients was smaller (P=0.026). The ratio of average SLP-RNFLT to average OCT-RNFLT was smaller in NAION than in PE (P=0.001) patients. Conclusion: In the setting of RNFL thickening, despite increased light retardance in PE and ON eyes, SLP revealed that NAION eyes have less retardance, possibly associated with ischemic axonal loss. Keywords: optic disc swelling, scanning laser polarimetry, optical coherence tomography